Karakterisasi Geoteknik Fondasi Kandidat Tapak PLTN dengan Metode Seismik Refraksi - Haryanto, Dwi; Rachael, Yoshi; Kamajati, Dhatu; Prasetyo, Gagah Hari; Syaeful, Heri; Indrastomo, Frederikus Dian (BRIN Publishing, 2021)
Presidential Regulation (Perpres) number 38 of 2018 concerning the National Research Master Plan for 2017–2045, the Government of Indonesia establishes several main areas that will become national research priorities, one of which is the energy sector. In the research theme of electricity technology based on new and renewable low/zero carbon energy, there is the topic of research on commercial-scale Nuclear Power Plant (NPP) technology. On the research topic, it was determined that within the research period of 2020–2024, a prototype nuclear power plant would be produced. Research related to the geotechnical characterization of the nuclear power plant site using the seismic refraction method was carried out to complement the previous research data. The purpose of this study was to determine the subsurface rock layer profile for estimation of work related to nuclear power plant foundations. Geological mapping and geophysical data acquisition, processing, as well as soil/rock interpretation based on the compression wave velocity (Vp) parameter are carried out to achieve this goal. The results of geological mapping show that there are 2 igneous rock units, namely quartz diorite and andesite. The results of processing and interpreting seismic refraction data produced a cross-sectional model of Vp in the subsurface rock layers. There are 3 rock layers in the research location, namely soil layer (Vp = 361–715 m/s), weathered igneous rock layer (Vp = 1.386–2,396 m/s), and fresh igneous layer (Vp = 3.789–6.133 m/s). The estimated density of fresh igneous rock based on calculations is 2.43–2.74 g/cm3. The modeling results can show the depth and structure of the subsurface layer of fresh igneous rock that can be the foundation of nuclear power plants.